BUDAYA POPULER DALAM NOVEL KAMI (BUKAN) SARJANA KERTAS KARYA J.S. KHAIREN (SOSIOLOGI SASTRA) - Hendriyanto, Agoes; Hendriyansyah, Muhamad Devi; Setyowati, Eny (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to determine the form of popular culture of hedonism and materialism contained in the novel Kami (Not) Sarjana Kertas by J.S Khairen in terms of the sociology of literature. Qualitative research with the object of study is a novel with the title